STRATEGI NAFKAH PETANI TERHADAP ALIH FUNGSI LAHAN PERTANIAN - Novikarumsari, Nurul Dwi; Adelia, Nanda; Oktadianti, Riri Qonita; Asyifa, Muhammad; Prawira, Dennys Gusti; Yusvianto, Annur Galih; Setyawan, Sigit Agung Kharis (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2020)
Nowadays, land conversion become a problem for farmers, because its can cut off the farmers economy. The main problem due to agricultural land decrease is difficult to find another job or a new job. The purpose of this study are to analyze agricultural land use and farmers' livelihood strategies for land conversion in Karangrejo Village, Sumbersari Subdistrict, Jember District . This research is a qualitative study using purposive location determination method. Data collection methods in this study are indepth interviews, observation, and documentation. Data analysis using Miles and Huberman. The research results are (1) horizontal and vertical agricultural land use, (2) the application of farmers' livelihood strategies is a dual income strategy.